The Wombs of Women : Race, Capital, Feminism - Verges, Françoise, 1952- (Theory in forms., 2020)
"THE WOMBS OF WOMEN, originally published in France in 2017 as Le Ventre des femmes, and translated into English by French and Africana studies scholar Kaiama Glover, is Françoise Verges's examination of the 1970s scandal in Reunion upon the discovery that doctors had performed thousands of abortions on Reunionese women without their knowledge, and had collected Social Security reimbursements by over-reporting and falsifying medical costs. For Verges, the scandal and its aftermath-in which the doctors responsible received minimal to no legal or criminal repercussions, and the Reunionese women received no reparations-exemplifies the coloniality of power in French overseas departments in the postcolonial era. In this book, one of Verges's primary aims is to interrogate the French definition of the "postcolonial," positing the postcolonial not as a temporality but rather a set of practices and politics that took (and continue to take) place in the wake of the empire's supposed dissolution. Postcoloniality, according to Verges, is therefore not the end of the colonial relationship but a re-imagining of the colonial territory into French constituencies and "overseas" departments, and is the condition which allowed for the abuse and violence against Reunionese women to take place. In particular, Verges examines the history of racialized capitalism in Reunion, and the changing discourses of birth control and population management in France and the overseas territories that occured in the transitional moment from colonial to postcolonial. Additionally, this book seeks to intervene in the raced and classed constructions of French feminism and to ask why the voices of women from the overseas departments rarely appear in French feminist analysis. Chapter 1 offers a detailed account of the events surrounding the forced abortions and sterilization of Reunionese women. Chapters 2 and 4 provide historical context for understanding the transition from colonial to postcolonial in the overseas departments, and how population management came to define the postcolonial condition of Reunion. Chapter 3 foregrounds the workings of racial capitalism, and specifically how the wombs of black women are raced. Chapter 5 intervenes in constructions of French feminism and centers the experiences of women living in the French overseas departments. This book will be of interests to scholars of feminism; colonial, postcolonial, and decolonial studies; French studies; African studies; and critical ethnic studies"--